2015
DOI: 10.2214/ajr.13.12325
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Ultrasound-Guided Cryoablation of Invasive Ductal Carcinomas up to 15 mm With MRI Follow-Up and Subsequent Surgical Resection

Abstract: OBJECTIVE The purpose of this study was to evaluate the effectiveness of ultrasound-guided cryoablation in treating small invasive ductal carcinoma and to assess the role of contrast-enhanced (CE) MRI in determining the outcome of cryoablation. SUBJECTS AND METHODS Twenty consecutive participants with invasive ductal carcinomas up to 15 mm, with limited or no ductal carcinoma in situ (DCIS), underwent ultrasound-guided cryoablation. Preablation mammography, ultrasound, and CE-MRI were performed to assess eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Cryoablation is widely accepted as the treatment for tumors in several organs (kidney, prostate, liver) [2][3][4]. Increasing numbers of studies have reported the feasibility and short-time outcomes of cryoablation of early breast cancer [5][6][7][8][9]. Additionally, two clinical phase-2 trials (NCT01992250, NCT02200705) to investigate complete response and local recurrence rates after cryoablation of early breast cancer are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Cryoablation is widely accepted as the treatment for tumors in several organs (kidney, prostate, liver) [2][3][4]. Increasing numbers of studies have reported the feasibility and short-time outcomes of cryoablation of early breast cancer [5][6][7][8][9]. Additionally, two clinical phase-2 trials (NCT01992250, NCT02200705) to investigate complete response and local recurrence rates after cryoablation of early breast cancer are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The precise needle positioning at the deep part of the tumor and the subsequent injection of the dye before needle cooling could be adjusted for each case through IOUS. 38 This start freeze-and-inject drug delivery strategy, which prevents the tracer from penetrating the frozen tumor, distributes a smaller volume of dye intratumor compared to a start inject-and-freeze delivery sequence, which would distribute a grander dye volume into the unfrozen tumor before freezing. Previous study 36 has demonstrated that such cryo-assisted drug delivery strategy has no effect on the intra- or extratumoral dye distribution.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that cryoablation was technically feasible and well tolerated by patients, although a clinical failure rate of 15% was observed. Interestingly, the authors highlighted that technical failures occurred when DCIS component was outside the cryoablation field 31…”
Section: Cryoablation For Early Breast Cancermentioning
confidence: 99%
“…Literature search reveals a high heterogeneity on this topic. Some studies enrolled a small number of patients at various stages of disease,18,33 in others surgical tumor removal was performed after cryoablation,31,34 and in others again percutaneous ablation was the only modality of treatment,6,35 thus reliable conclusions on the usefulness of cryoablation in the subgroup with early breast cancer could not be drawn.…”
Section: Cryoablation For Early Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation